2015
DOI: 10.1021/jo502898s
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of Anion and Cation Effects on the Keto–Enol Equilibrium in Ionic Liquids. A Comparative Study with Conventional Solvents

Abstract: A comparative thermodynamic investigation of the keto-enol interconversion reaction has been performed in several organic solvents and room-temperature ionic liquids (RTILs) to evaluate the role of the solvent and the effect of the ionic composition of RTILs. The tautomeric constant (KT) values at different temperatures have been analyzed in terms of the van't Hoff relationship to give the relevant thermodynamic parameters. The ΔG° values are the results of quite different combinations of the ΔH° and ΔS° value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A successful route towards gaining a deeper understanding is through the study of ILs with different compositions. A lot of effort has been made to study cation behavior, whereas recent studies of anion effects also reveal distinct solvation properties . In brief, some results indicated that apolar solutes such as benzene are better dissolved in ILs that have larger anions such as bis(trifluoromethanesulfonyl)imide (TFSI) or smaller cation/anion size ratios .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A successful route towards gaining a deeper understanding is through the study of ILs with different compositions. A lot of effort has been made to study cation behavior, whereas recent studies of anion effects also reveal distinct solvation properties . In brief, some results indicated that apolar solutes such as benzene are better dissolved in ILs that have larger anions such as bis(trifluoromethanesulfonyl)imide (TFSI) or smaller cation/anion size ratios .…”
Section: Introductionmentioning
confidence: 99%
“…Al ot of effort has been made to study cation behavior, [28][29][30][31][32][33][34][35] whereas recent studies of anion effects also reveal distinct solvationp roperties. [21,[36][37][38][39][40][41][42][43][44][45][46][47][48] In brief, some resultsi ndicated that apolar solutes such as benzene are better dissolved in ILs that have larger anions such as bis(trifluoromethanesulfonyl)imide (TFSI) or smaller cation/ anion size ratios. [38] Nevertheless, it is not clear if this finding is of general validity or related to the properties of the molecular solute.…”
Section: Introductionmentioning
confidence: 99%
“…Data collected in ILs seem to indicate that the thermodynamics of the above reaction is influenced mainly by the nature of the IL ions, with the anion playing a major role, as well as by the alkyl chain segregation in the heterogeneous organisation of ILs . Moreover, the reaction is faster in ILs than in conventional organic solvents, with rate constants higher than those expected on the basis of the p K a values .…”
Section: Introductionmentioning
confidence: 83%
“…[29] Data collected in ILs seem to indicate that the thermodynamics of the above reactioni si nfluencedm ainly by the nature of the IL ions, with the anion playing am ajor role, as well as by the alkyl chain segregationint he heterogeneouso rganisation of ILs. [25] Moreover, the reactioni sf aster in ILs than in conventional organic solvents, with rate constantsh igher than those expected on the basis of the pK a values. [26] This result could suggest ah igher basicity of the catalysti nI Ls than in conventional organic solvents but we werea ware that the pK a values collected in aqueous solution do not adequately describe the acid-base strength of speciesi nI Ls, [22,30] due to the peculiar IL-solute interactions.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation